The comparison of the effects and side effects of local anesthetic and opioid combinations in epidural patient controlled analgesia - (:unkn) unknown (My University, 2005)
The aim of this study was to retrospectively evaluate the efficacy and side effects of local anesthetic and opioid combinations in 457 patients who have received epidural patient-controlled analgesia (EPCA). Hemodynamic parameters, numeric rating scale, sedation scores, the degree of motor and sensory blockage, the presence of side effects, the parameters of PCA device were recorded from the postoperative pain records. 253 patients received 0.1 % bupivacaine + 3 microg/ml fentanyl (Group B1F3), 80 patients received 0.125 % bupivacaine + 3 microg/ml fentanyl (Group B12F3), 43 patients received 0.125 % bupivacaine + 4 microg/ml fentanyl (Group B12F4), 46 patients received 0.1 % bupivacaine + 0.1 mg/ml morphine (Group B1M1) and 35 patients received 0.125 % bupivacaine + 0.1 mg/ml morphine (Group B12M1). Nausea was significantly higher in group B1M1 compared to B12F3, in group B12M1 compared to B1F3 and B12F3 (p<0.05), vomiting was significantly higher in group B1M1 and B12M1 (p<0.05) compared to B12F3, pruritus was significantly higher in group B12F4 compared to B12F3 and B1F3, in group B1M1 compared to B1F3 and B12F3 and in group B12M1 compared to B1F3 and B12F3 (p<0.05). As a result, in EPCA, the combination of bupivacaine and fentanyl provides as effective analgesia as the combination of bupivacaine and morphine and 3 mg/ml fentanyl admixture may be preferred with less side effects such as nausea, vomiting and pruritus.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Aged; Aged, 80 and over; Adolescent; Male; Retrospective Studies; Pain, Postoperative; Drug Therapy, Combination; Morphine; Anesthetics, Local; Analgesics, Opioid; Fentanyl; Bupivacaine; Analgesia, Patient-Controlled; Analgesia, Epidural